2008
DOI: 10.1111/j.1440-1754.2008.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Massachusetts Youth Screening Instrument to assess mental health problems in young people within an Australian youth detention centre

Abstract: This study confirmed the high rates of mental health problems in adolescents within youth detention. Appropriate use of screening tools improves our understanding and targets treatment of mental health problems in this cohort. We have reservations in recommending the MAYSI-2 as a valid screening tool for Indigenous young people in youth detention and recommend the development of a more appropriate screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 25 publications
5
31
2
2
Order By: Relevance
“…Over a 6-month period 96 of the 212 Indigenous people recepted were screened with the MAYSI 2, a 52-item mental health screening tool developed for youth in the criminal justice system in the United States. 27 Over 80% of the Indigenous youth that were screened scored above the cut off for a mental health problem (59% drug and alcohol, 29% anger problems, 25% depressions/anxiety, 30% somatic complaints, 15% suicide ideation and 25% thought disturbance). The study also found that nearly 20% of Indigenous males and 55% of Indigenous females reported significant exposure to traumatic experiences.…”
Section: Evidence On the Topic Custody: Mental Illness And Traumamentioning
confidence: 99%
“…Over a 6-month period 96 of the 212 Indigenous people recepted were screened with the MAYSI 2, a 52-item mental health screening tool developed for youth in the criminal justice system in the United States. 27 Over 80% of the Indigenous youth that were screened scored above the cut off for a mental health problem (59% drug and alcohol, 29% anger problems, 25% depressions/anxiety, 30% somatic complaints, 15% suicide ideation and 25% thought disturbance). The study also found that nearly 20% of Indigenous males and 55% of Indigenous females reported significant exposure to traumatic experiences.…”
Section: Evidence On the Topic Custody: Mental Illness And Traumamentioning
confidence: 99%
“…On the SI scale, girls (29%) had a much higher prevalence of scoring above Caution than boys (15%). The pattern of girls consistently scoring higher than boys on the SI scale repeated in the numerous other studies where gender was examined (e.g., Archer et al, 2010;Archer, Stredny, Mason, & Arnau, 2004;Cauffman, 2004;Gretton & Clift, 2011;Hayes, McReynolds, & Wasserman, 2005;Kerig, Moeddel, & Becker, 2011;Nordness et al, 2002;Stathis et al, 2008;Wasserman et al, 2004).…”
Section: Past Maysi-2 Si Scale Research Findingsmentioning
confidence: 92%
“…Most suffer from some form of mental health problem (Bickel & Campbell, 2002;Indig et al, 2011;Sawyer et al, 2010;Stathis et al, 2008). Yet mental health services for young people in Australia's youth detention centres have historically been fragmented.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…Although the Massachusetts Youth Screening Instrument-2 (MAYSI-2) (Grisso, Barnum, Fletcher, Cauffman, & Peuschold, 2001) is now well accepted in the USA, concerns have been raised about its validity in the Australian population, particularly for Indigenous youth (Stathis et al, 2008). We are aware of no valid, reliable psychological tools that have been specifically developed for the screening of suicide risk, mental disorders or substance abuse within the Australian adolescent forensic population.…”
Section: The Challenge Of Building An Evidence Basementioning
confidence: 98%